The Role of Social Media and Parental Interpersonal Communication with Premarital Sexual Behavior in Adolescents - Andriani, Rininta; Dina Cahyani; La Ode Syaiful Islami; Jamal Harimuddin (Window of Health : Jurnal Kesehatan, 2025)
The phenomenon of premarital sexual behavior in Indonesia is increasingly prevalent among adolescents, including in the city of Baubau. One of the reasons is the easy access to pornography on social media. Therefore, the role of parents is needed in supervising and guiding adolescents. This study aimed to determine the role of social media and parents' interpersonal communication with premarital sexual behavior in adolescents in Baubau city. This study used a qualitative research method with a case study approach. Informants were selected by purposive sampling and snowball sampling, totaling 8 teenagers (5 male teenagers and 3 female teenagers) as a key informants. The results of this study show that both male and female adolescents admit that their sexual behavior is inspired or learned through the pornography they watch. However, exposure to pornography through social media is more dominant in contributing to the sexual behavior of female adolescents than male adolescents, because male adolescents prefer to watch pornography through online websites. Interpersonal communication generally went well, where there was empathy, support, and equality. However, the aspect of openness between adolescents and parents regarding sexuality issues does not seem to be fully explored. On the other hand, the positive attitude of parents who give too much freedom to children actually makes adolescents fall into bad sexual behavior. Other factors that influence premarital sexual behavior in adolescents are knowledge, attitudes, peers and level of religiosity. The conclusion in this study is that social media and parental interpersonal communication have a role in premarital sexual behavior in adolescents.